Penerapan Arsitektur Kontemporer Pada Perancangan Banten Creative Hub Di Pagedangan Kabupaten Tangerang - Mella Putri Ayu; Sri Kurniasih (MAESTRO, 2019)
Banten Creative Hub or Banten Creative Center is a place that is used as a place to develop a creative idea and as a place to learn, people will make prototypes or examples of products that are not to be mass produced. Contemporary architecture is a form of architectural work that is happening in the present that aims to demonstrate a certain quality especially in terms of technological progress and also the freedom to express an architectural style, trying to create a situation that is separate from a non-uniform community